2016
DOI: 10.1044/2015_jslhr-l-14-0266
|View full text |Cite
|
Sign up to set email alerts
|

Video Feedback in Key Word Signing Training for Preservice Direct Support Staff

Abstract: Results suggest that at an equal time investment, the programs containing more training components were more effective. Research on the effect of rehearsal on signing maintenance is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…( 2017)foundthatcollegestudentswhoreceived videofeedbackregardingtheirerrorsorcorrectuseofASLhadgreatersigningimprovementandthat studentspreferredtime-synchronizedfeedbackwithgreaterbenefitfromsignsvisuallyillustrated. Likewise, Rombouts et al (2016) found that college students learning ASL achieved higher key wordsigningaccuracywithvideofeedbackwhencomparedtostudentswhoreceivedmodellingand verbalfeedback.WhileallofthesestudiesusedvideotolearnorimproveASL,nonefeaturedthe usevideoonmobiledevices.…”
Section: American Sign Language and Videomentioning
confidence: 88%
“…( 2017)foundthatcollegestudentswhoreceived videofeedbackregardingtheirerrorsorcorrectuseofASLhadgreatersigningimprovementandthat studentspreferredtime-synchronizedfeedbackwithgreaterbenefitfromsignsvisuallyillustrated. Likewise, Rombouts et al (2016) found that college students learning ASL achieved higher key wordsigningaccuracywithvideofeedbackwhencomparedtostudentswhoreceivedmodellingand verbalfeedback.WhileallofthesestudiesusedvideotolearnorimproveASL,nonefeaturedthe usevideoonmobiledevices.…”
Section: American Sign Language and Videomentioning
confidence: 88%
“…Their rationale was that it is necessary to embed AAC in the community. However, Rombouts, Meuris, Maes, De Meyer, and Zink () used video feedback and a photograph reminder card with participants in their KWS training. Our training consisted of a one‐day workshop with a fixed vocabulary and a de facto follow‐up due to the data collection of the study, which reinforced the need to practise and remember the signs for each round of testing.…”
Section: Discussionmentioning
confidence: 99%
“…() and Rombouts et al. () indicate that maintenance of sign knowledge after training is problematic. Therefore, it is important to consider alternate ways of ensuring that both sign knowledge at Kirkpatrick level 2 (the number of signs that the person is able to recognise or use) and implementation of sign at Kirkpatrick level 3 (using it successfully with the person who needs it) are considered.…”
Section: Discussionmentioning
confidence: 99%
“…Aunque muchos docentes, gestores y padres son conscientes de la necesidad de cambiar ciertos aspectos de la organización de las aulas y del rol que ejerce el docente, con el fin de promover el desarrollo de la comunicación y el lenguaje de los alumnos, este aspecto continúa constituyendo un reto debido a su complejidad (Fernández y Malvar, 1999;Vega et al, 2018). Conseguir que un aula llegue a ser un entorno favorable para el desarrollo de la comunicación y el lenguaje no es tarea fácil, si no se fomenta que los docentes inicien procesos reflexivos sobre su propia práctica, mediante programas de asesoramiento colaborativo (Neuman y Cunningham, 2009;Rudd, Lambert, Satterwhite y Smith, 2009). Los resultados parecen indicar que el programa de asesoramiento diseñado e implementado en esta investigaciónacción colaborativa es una herramienta útil para ayudar a los docentes a construir un entorno apropiado para promover el desarrollo de la competencia comunicativa de sus alumnos, dando lugar a cambios en la organización del aula, en el diseño instruccional y en las características del estilo interactivo con sus alumnos.…”
Section: Conclusiones Y Futuras Líneas De Investigaciónunclassified